Peningkatan Kemampuan Pemahaman Konsep Matematis Siswa SMA melalui Penggunaan Model Pembelajaran Inkuiri - fera noviawati; Nitta Puspitasari (LPPM Universitas Advent Indonesia, 2023)
The ability to understand mathematical concepts is one of the abilities that must be possessed by students. A concept if understood properly and correctly will lead students to a meaningful learning process. Applying the inquiry learning model to the learning process is one way to improve the ability to understand mathematical concepts. The purpose of this study was to find out whether there is a significant difference in the increase in the ability to understand mathematical concepts between students who receive the inquiry learning model and the conventional learning model. The research method used is quasi-experimental. The population in this study were students of class X SMA Negeri 22 Garut. The samples used were class X MIPA-3 as the experimental class and X MIPA-4 as the control class with a total of 34 students in each class. The sampling technique uses cluster sampling. The instrument used was a written test in the form of an essay. Data collection techniques using tests, observation, and documentation. Testing the hypothesis with a non-parametric test (Mann Whitney test). The results of this study indicate that there is a significant difference in increasing the ability to understand mathematical concepts between students who use the inquiry learning model and conventional learning models.